Improvement of Deltaic Lateritic Soil using River Sand and Cement for use as Pavement Construction Material (Nigerian Journal of Technology, 2021)
This study examined the effect of mechanical and chemical improvement on deltaic lateritic soils in Warri East in Delta State, Nigeria. Mechanical stabilization was carried out by adding river sand to the natural soil in various proportions, while chemical stabilization was carried out using cement and a mixture of cement and sand. Compaction and CBR tests were conducted on the natural soil before and after stabilization. From the results obtained, it was seen that the mechanical stabilization method improved the strength properties of the soil making it suitable for use as subbase materials, though not as much as the chemical stabilization method or the mixed method of stabilization. It was concluded that using a combination of cement and sand as a stabilizing agent for deltaic lateritic soils can lead to significant reduction in the amount of cement required for soil stabilization thus saving costs.http://dx.doi.org/10.4314/njt.v40i2.1